Strategi Asertif dalam Konstruksi Kritik dan Argumentasi pada Peristiwa Tutur Digital Podcast Malaka Project - Hayati, Hasna Arridha; Efendi, Anwar; Hartono, Hartono (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2026)
The rise of podcasts as a digital communication medium has created a space for speakers to express criticism, viewpoints, and arguments through the use of assertive speech acts. This study aims to analyze the construction of criticism and argumentation through the use of assertive speech acts in the utterances of Bagus Muljadi and Ferry Irwandi in the Malaka Project podcast episode “Discussing Research, Education, and Mystical Logic with Bagus Muljadi.” This study employs a qualitative descriptive approach, with data collected through the technique of non-participatory listening, recording, and note-taking, while data validity is strengthened through the application of triangulation. The data were analyzed using the matching and distribution methods, supplemented by stages of reduction, presentation, and verification to ensure the accuracy of classification. The results of the study revealed 207 assertive speech acts, including 42 declarative utterances, 22 propositional utterances, 6 boastful utterances, 42 complaints, 59 expressions of opinion, and 36 reports. The research findings indicate that speakers use assertive speech acts to construct criticism of issues in education and research, while simultaneously strengthening their arguments in digital communication. The use of these six forms of assertive speech acts reflects the dynamics of digital communication, which not only serves to convey information but also functions as a means of constructing criticism and arguments in podcast-based communication spaces. The results of this study contribute to the development of pragmatic studies, particularly in understanding the function of assertive speech acts as a strategy for constructing criticism and arguments in podcast-based digital communication.